2016
DOI: 10.1016/j.neulet.2016.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cx32 expression in spinal cord TrkB oligodendrocytes following peripheral axon injury

Abstract: Following injury to motor axons in the periphery, retrograde influences from the injury site lead to glial cell plasticity in the vicinity of the injured neurons. Following the transection of peripherally located preganglionic axons of the cervical sympathetic trunk (CST), a population of oligodendrocyte (OL) lineage cells expressing full length TrkB, the cognate receptor for brain derived neurotrophic factor (BDNF), is significantly increased in number in the spinal cord. Such robust plasticity in OL lineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These divergent results may be explained by the fact that the CC1 + oligodendrocytes that were upregulated in the 5xFAD spinal cord likely do not share the same cell lineage identity as the CC1 + population that was found depleted in the brain of the 5xFAD model and could originate from heterogeneous polydendrocytes with differentiation capacity [ 63 , 64 ]. Interestingly, another study reported rapid proliferation of oligodendrocytes from a distinct type of TrkB oligodendrocyte lineage (OL), suggesting that glial cells in the spinal cord encounter different communication dynamics than those in the brain, and in response to peripheral traumatic injuries, they could be triggered to multiply [ 65 ]. These compelling findings indicate that in the same AD model, the oligodendroglial Gx47 GJs reflect a different and complex region-specific behavior that might imply the involvement of different regulatory pathways and signaling molecules driven by AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…These divergent results may be explained by the fact that the CC1 + oligodendrocytes that were upregulated in the 5xFAD spinal cord likely do not share the same cell lineage identity as the CC1 + population that was found depleted in the brain of the 5xFAD model and could originate from heterogeneous polydendrocytes with differentiation capacity [ 63 , 64 ]. Interestingly, another study reported rapid proliferation of oligodendrocytes from a distinct type of TrkB oligodendrocyte lineage (OL), suggesting that glial cells in the spinal cord encounter different communication dynamics than those in the brain, and in response to peripheral traumatic injuries, they could be triggered to multiply [ 65 ]. These compelling findings indicate that in the same AD model, the oligodendroglial Gx47 GJs reflect a different and complex region-specific behavior that might imply the involvement of different regulatory pathways and signaling molecules driven by AD pathology.…”
Section: Discussionmentioning
confidence: 99%